1996
DOI: 10.1017/s0950268800001175
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal meningitis in the North East Thames Region UK: epidemiology and molecular analysis of isolates

Abstract: SUMMARYOne hundred and fourteen cases of pneumococcal meningitis were identified by prospective laboratory based surveillance during 1990-3 in the North East Thames Region. Higher rates of disease were seen in Asians (2' 1 / 100000) than Caucasians (0 8/ 100000) (P = 0 002). The incidence of meningitis was higher in children than adults, while mortality rates were highest in adults over the age of 60 (48 %). In 72 cases, both blood and CSF were culture positive. Serotyping of 65 isolates collected identified 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…We have demonstrated that the ST9 clone is 4.8 times more common in blood than in other sites and is therefore more invasive than the average S. pneumoniae isolate. The ST9 clone has also been identified as an important cause of meningitis throughout the United Kingdom (10,15,37), and this clone is now recognized as a cause of invasive disease in other countries (http://www.mlst.net). There are many virulence factors other than the capsule involved in the pathogenesis of pneumococcal infection (14), and there is evidence that particular strains of pneumococci have a predilection for blood and cerebrospinal fluid (16).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the ST9 clone is 4.8 times more common in blood than in other sites and is therefore more invasive than the average S. pneumoniae isolate. The ST9 clone has also been identified as an important cause of meningitis throughout the United Kingdom (10,15,37), and this clone is now recognized as a cause of invasive disease in other countries (http://www.mlst.net). There are many virulence factors other than the capsule involved in the pathogenesis of pneumococcal infection (14), and there is evidence that particular strains of pneumococci have a predilection for blood and cerebrospinal fluid (16).…”
Section: Discussionmentioning
confidence: 99%
“…Former patients were identified from active surveillance for invasive S. pneumoniae disease in the Oxford and North East Thames regions of the UK [27,30]. Patients were defined as either (1) the isolation of S. pneumoniae from the cerebrospinal fluid (CSF) or (2) Gram-positive diplococci seen on Gram stain of a CSF sample in patients presenting with a clinical picture of meningitis.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial isolates were selected from those submitted to the Health Protection Agency in 2002 as well as from collections previously described [23][24][25][26]. Mutation frequencies were deter- b Resistance to erythromycin (ERY), sulphonamide (SUL), trimethoprim (TMP), chloramphenicol (CHL), penicillin (PEN), tetracycline (TET), streptomycin (STR), ciprofloxacin (CIP) and azithromycin (AZM), as described in Ref.…”
Section: Bacterial Isolates and Culturementioning
confidence: 99%